2021
DOI: 10.1002/hbm.25426
|View full text |Cite
|
Sign up to set email alerts
|

Microstates in complex and dynamical environments: Unraveling situational awareness in critical helicopter landing maneuvers

Abstract: Understanding decision‐making in complex and dynamic environments is relevant for designing strategies targeting safety improvements and error rate reductions. However, studies evaluating brain dynamics in realistic situations are scarce in the literature. Given the evidence that specific microstates may be associated with perception and attention, in this work we explored for the first time the application of the microstate model in an ecological, dynamic and complex scenario. More specifically, we evaluated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
2
14
0
1
Order By: Relevance
“…Various studies implied that the dynamic properties of EEG microstates can effectively reflect the change of brain state when operators were performing tasks. Deolindo [34] found that the dynamic properties of microstates can be used to distinguish the situation awareness levels of helicopter pilots. Krylova's research showed that the microstate metrics were statistically correlated with the vigilance level of human [35].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies implied that the dynamic properties of EEG microstates can effectively reflect the change of brain state when operators were performing tasks. Deolindo [34] found that the dynamic properties of microstates can be used to distinguish the situation awareness levels of helicopter pilots. Krylova's research showed that the microstate metrics were statistically correlated with the vigilance level of human [35].…”
Section: Introductionmentioning
confidence: 99%
“…The rst study investigating the BOLD correlates of EEG microstates found them to be associated with both increases and decreases in the bold signal (Britz, Van De Ville, & Michel, 2010). Deolindo et al observed that a microstate class associated with activation of the medial prefrontal cortex and attentional functions decreased while helicopter pilots conducted complex and potentially life-threatening maneuvers (Deolindo et al, 2021). Rajkumar et al…”
Section: Discussionmentioning
confidence: 99%
“…Here we report on the analyzed data from the EDA, and heartbeat and breathing frequency of the pilots. The EEG data is presented elsewhere 37 .…”
Section: Methodsmentioning
confidence: 99%